2009
DOI: 10.1103/physrevd.79.024014
|View full text |Cite
|
Sign up to set email alerts
|

On gravitational waves in spacetimes with a nonvanishing cosmological constant

Abstract: We study the effect of a cosmological constant Λ on the propagation and detection of gravitational waves. To this purpose we investigate the linearised Einstein's equations with terms up to linear order in Λ in a de Sitter and an anti-de Sitter background spacetime. In this framework the cosmological term does not induce changes in the polarization states of the waves, whereas the amplitude gets modified with terms depending on Λ. Moreover, if a source emits a periodic waveform, its periodicity as measured by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…As it is well known, Λ does not introduce any additional polarization states for GWs [40]. Therefore, we can conclude that GWs in the f (R, T φ ) = −R/4 + 2λT φ theory have only the two usual polarizations of GR, i.e., + and ×.…”
Section: F (R T ) Gravitysupporting
confidence: 58%
See 1 more Smart Citation
“…As it is well known, Λ does not introduce any additional polarization states for GWs [40]. Therefore, we can conclude that GWs in the f (R, T φ ) = −R/4 + 2λT φ theory have only the two usual polarizations of GR, i.e., + and ×.…”
Section: F (R T ) Gravitysupporting
confidence: 58%
“…However, it has already been shown that a CC does not introduce any additional polarization states for GWs (see Ref. [40]). …”
Section: Discussionmentioning
confidence: 97%
“…we compare the trace of (29) with (30), it turns out that the scalar perturbation δφ has to vanish identically. Therefore, as it can be seen by (37) and (38), this condition compels the breathing mode to disappear as well and allows us to rescue the traceless condition oñ h µν . Thus, the two standard polarizations are restored, in agreement with the Palatini formulation of gravitational waves [36,37].…”
Section: Gravitational Waves In the Presence Of The Immirzi Fieldmentioning
confidence: 75%
“…Therefore, as it can be seen by (37) and (38), this condition compels the breathing mode to disappear as well and allows us to rescue the traceless condition oñ h µν . Thus, the two standard polarizations are restored, in agreement with the Palatini formulation of gravitational waves [36,37]. Furthermore, since the geometrical scalar perturbation δφ is forced to vanish in linearized theory, the contorsion tensor simply reduces to a completely antisymmetric tensor, that is:…”
Section: Gravitational Waves In the Presence Of The Immirzi Fieldmentioning
confidence: 75%
“…If f (R) = αR 2 , it can be shown that the associated theory actually corresponds to GR with a cosmological constant [26], which yields the two usual tensorial polarization modes + and × [27].…”
Section: Polarization Modes In Palatini Formalismmentioning
confidence: 99%